English Teachers’ Strategies in Addressing Students’ Low Reading Ability: A Case Study in Indonesian Junior High School - Andin Audina Dwiutami Rahman; Maya Rahmawati; Iwan Ridwan (Journal of Educational Sciences, 2026)
Reading ability plays a pivotal role in English as a Foreign Language (EFL) learning. However, many junior high school students in Indonesia continue to struggle with reading comprehension, vocabulary recognition, and pronunciation. This study explores the strategies employed by English teachers to support students with low reading ability. Conducted at a public junior high school in Majalengka, West Java, this qualitative case study involved two English teachers and used interviews, classroom observations, and document analysis to gather data. The findings revealed that teachers employed a range of strategies, including read-aloud and guided reading, vocabulary repetition, peer pairing, visual aids and the use of dictionaries. These strategies were primarily intuitive and adapted to classroom conditions rather than being formally differentiated. While the techniques proved helpful in scaffolding struggling students, the study also highlights the lack of challenge for higher-level learners. This paper recommends more systematic application of differentiated instruction to address the varied needs of learners and improve reading instruction in heterogeneous classrooms.